2004
DOI: 10.1038/sj.emboj.7600476
|View full text |Cite
|
Sign up to set email alerts
|

FOXO transcription factor activation by oxidative stress mediated by the small GTPase Ral and JNK

Abstract: Forkhead transcription factors of the FOXO class are negatively regulated by PKB/c-Akt in response to insulin/IGF signalling, and are involved in regulating cell cycle progression and cell death. Here we show that, in contrast to insulin signalling, low levels of oxidative stress generated by treatment with H 2 O 2 induce the activation of FOXO4. Upon treatment of cells with H 2 O 2 , the small GTPase Ral is activated and this results in a JNK-dependent phosphorylation of FOXO4 on threonine 447 and threonine 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
613
5
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(646 citation statements)
references
References 43 publications
23
613
5
5
Order By: Relevance
“…As high and very low levels of ROS lead to impaired cellular functions, maintaining intracellular ROS homeostasis is essential to prevent pathological processes including cancer and other age‐associated diseases. FOXOs are regulated by oxidative stress via changes in upstream FOXO regulatory pathways or directly sensing the cellular redox status through reversible oxidation and reduction of cystein residues (Essers et al ., 2004; Eijkelenboom & Burgering, 2013; Putker et al ., 2013). FOXO factors regulate the expression of the key detoxification enzymes MnSOD (manganese superoxide dismutase), catalase, and GADD45 (Kops et al ., 2002; Nemoto & Finkel, 2002).…”
Section: Foxo and Resistance To Oxidative Stressmentioning
confidence: 99%
“…As high and very low levels of ROS lead to impaired cellular functions, maintaining intracellular ROS homeostasis is essential to prevent pathological processes including cancer and other age‐associated diseases. FOXOs are regulated by oxidative stress via changes in upstream FOXO regulatory pathways or directly sensing the cellular redox status through reversible oxidation and reduction of cystein residues (Essers et al ., 2004; Eijkelenboom & Burgering, 2013; Putker et al ., 2013). FOXO factors regulate the expression of the key detoxification enzymes MnSOD (manganese superoxide dismutase), catalase, and GADD45 (Kops et al ., 2002; Nemoto & Finkel, 2002).…”
Section: Foxo and Resistance To Oxidative Stressmentioning
confidence: 99%
“…Furthermore, the MST1-FOXO pathway has a significant role in drug treatment-induced cancer cell death (38). When cells are under to oxidative stress, the JNK-dependent signaling pathway causes phosphorylation of FOXO4, thereby inducing FOXO4 nuclear translocation and activity (39). JNK mediates the FOXO activity via the correct assembly of JNK interacting protein 1 (JIP1) complexes, which includes three substrates, mitogen-activated protein kinase (MAPK) kinase kinase 11, MAPK kinase 4 and JNK.…”
Section: Mammalian Sterile 20-like Kinase (Mst) and Jun-n-terminal Kimentioning
confidence: 99%
“…Furthermore, it has been demonstrated that JNK-1 directly interacts with, phosphorylates, enhances nuclear localization of DAF-16, and induces its target gene expression [24]. Indeed, low levels of oxidative stress generated by treatment with H 2 O 2 activates the small GTPase Ral and induce a JNK-dependent phosphorylation of Threonine 447 and Threonine451, nuclear translocation, and transcriptional activation of FOXO4 [26].…”
Section: Regulation Of Foxos By Other Signaling Pathwaysmentioning
confidence: 99%